INNOVATIVE METHODS OF TEACHING STUDENTS WITH DIFFERENT KNOWLEDGE AND SKILLS IN ONE GROUP (Ustozlar uchun, 2024)
The process of renewal and modernization in the field of education in our country is a continuous process of all links of the education system, including the training of mature specialists who can meet the requirements of the times in higher education, the formation of new knowledge and skills in them, their own working on it requires improving the ability to purposefully use the achievements of modern technology. In the preparation of future primary school teachers based on today's requirements, the science "Technology and its teaching methodology" occupies an important place in the fulfillment of priority tasks. Based on the main scientific-theoretical and practical results of the subject, the future specialist teachers will have the skills to develop hard work, discipline, responsibility, sense of duty, and creativity.